1998
DOI: 10.1002/(sici)1097-0142(19980315)82:6<1160::aid-cncr22>3.0.co;2-3
|View full text |Cite
|
Sign up to set email alerts
|

Detection of unknown occult primary tumors using positron emission tomography

Abstract: A previously unknown primary tumor was able to be identified with FDG-PET in 7 of 29 patients after an unsuccessful conventional diagnostic workup. However, the clinical relevance of PET information in this setting is limited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
97
0
16

Year Published

1999
1999
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 214 publications
(116 citation statements)
references
References 16 publications
2
97
0
16
Order By: Relevance
“…Newer imaging techniques (Tilanus-Linthorst et al, 1997; Kole et al, 1998;Lenzi et al, 1998;Schorn et al, 1999;Stevens et al, 1999), such as breast MRI, positron emission tomography and other nuclear medicine techniques, that can give clues as to the site of the primary, presently remain of limited help.…”
Section: Discussionmentioning
confidence: 99%
“…Newer imaging techniques (Tilanus-Linthorst et al, 1997; Kole et al, 1998;Lenzi et al, 1998;Schorn et al, 1999;Stevens et al, 1999), such as breast MRI, positron emission tomography and other nuclear medicine techniques, that can give clues as to the site of the primary, presently remain of limited help.…”
Section: Discussionmentioning
confidence: 99%
“…FDG-PET has proved to be a complementary study for patients with unknown primary tumor of the head and neck when conventional evaluation fails (Fig 2). [11][12][13][14][15][16][17][18] A review of 16 studies published between 1994 and 2003 evaluating the utility of FDG-PET in identifying unknown primary carcinomas af- PET/CT showed a 1.0 ϫ 1.2 cm hypermetabolic (gold arrow) and enhancing (red arrow) lesion at the right base of the tongue, large nodes in the right levels II/III, an 8-mm node at level IV, and no left-sided nodes or distant metastases. Direct laryngoscopy with biopsy and cervical esophagoscopy showed no lesions, but palpation showed a 1-cm firm right base of tongue lesion not crossing the midline, which was pathologically proved to be SCC.…”
Section: Detection Of Unknown Primary Tumormentioning
confidence: 99%
“…The reduced signal-to-noise ratio may be a reason. The detection of tumors with PET/CT depends on the difference between the intensity of the signal from the tumor and that of the background [10]. Another explanation is that the primary lesion has involuted and is not detectable when the metastasis becomes evident [22,23].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that positron emission tomography/ computed tomography (PET/CT) utilizing 18 F-Fluorodeoxyglucose (FDG) is a valuable tool in patients with CUP, but with large difference between studies from 24 to 80 percent of detection rates [8][9][10][11][12].…”
mentioning
confidence: 99%